Pengaruh Metode Pengeringan Terhadap Senyawa Volatil pada Pembentukan Flavor Biji Kopi Robusta - Jonathan Namora; M. Sihombing; M. Rahardjo (xxxx-xxxx, 2020)
Namora J. Sihombing M. Rahardjo M. 2020. effect of drying method on volatile compounds in the formation of robusta coffee beans flavor. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The coffee beans drying process still depended on conventional methods, while also influenced by an uncertain climate. This paper is aimed to review the coffee beans drying methods through conventional, greenhouse, cabinet, heat pump, and microwave drying methods upon the volatile compounds content, then get the best drying method. By GC-MS analysis with 0-40 minutes of retention time, founded 6 dominant compounds that are important within flavor formation, such methanethiol; 2,3-butadione; 2,3-pentadione; hexanal; 2-ethylpyrazine; and 2-ethyl-6-methylpyrazine. Seen from effectiveness of drying time, microwave become the best instrument to choose. However inefficient on breaking the precursor into volatile compounds, while heat pump dryer is the most effective method to reduce the water content. Meanwhile, it has ineffectiveness as microwave does. Drying cabinet is the most recommended method, due its temperature stability, and able to reach the effective temperature of Maillard reaction (>120 ˚C), the most important reaction on flavor’s characteristic formation.